RNA-directed DNA Methylation - Erdmann, Robert M.; Picard, Colette L. (PLoS genetics, 2020)
RNA-directed DNA methylation (RdDM) is a biological process in which non-coding RNA molecules direct the addition of DNA methylation to specific DNA sequences. The RdDM pathway is unique to plants, although other mechanisms of RNA-directed chromatin modification have also been described in fungi and animals. To date, the RdDM pathway is best characterized within angiosperms (flowering plants), and particularly within the model plant Arabidopsis thaliana. However, conserved RdDM pathway components and associated small RNAs (sRNAs) have also been found in other groups of plants, such as gymnosperms and ferns. The RdDM pathway closely resembles other sRNA pathways, particularly the highly conserved RNAi pathway found in fungi, plants, and animals. Both the RdDM and RNAi pathways produce sRNAs and involve conserved Argonaute, Dicer and RNA-dependent RNA polymerase proteins. RdDM has been implicated in a number of regulatory processes in plants. The DNA methylation added by RdDM is generally associated with transcriptional repression of the genetic sequences targeted by the pathway. Since DNA methylation patterns in plants are heritable, these changes can often be stably transmitted to progeny. As a result, one prominent role of RdDM is the stable, transgenerational suppression of transposable element (TE) activity. RdDM has also been linked to pathogen defense, abiotic stress responses, and the regulation of several key developmental transitions. Although the RdDM pathway has a number of important functions, RdDM-defective mutants in Arabidopsis thaliana are viable and can reproduce, which has enabled detailed genetic studies of the pathway. However, RdDM mutants can have a range of defects in different plant species, including lethality, altered reproductive phenotypes, TE upregulation and genome instability, and increased pathogen sensitivity. Overall, RdDM is an important pathway in plants that regulates a number of processes by establishing and reinforcing specific DNA methylation patterns, which can lead to transgenerational epigenetic effects on gene expression and phenotype.